Self-esteem, resilience and perceived social support among juvenile delinquents in Malaysian moral rehabilitation centers and their attitude towards acceptance of counselling - Sukumaran, Puspha; Mohd Noah, Sidek (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The purpose of this research is to evaluate the level of self-esteem, resilience and perceived social support among juvenile delinquents in Malaysian Moral Rehabilitation Centres and its effect on their attitude towards acceptance of counselling as a form of psychological help; a step towards change and assimilation into society later in life. There are programs and counsellors at these centres with the aim of providing the juvenile delinquents with needed guidance and assistance but do the practitioners understand the mental state of these juvenile delinquents in terms of their self-esteem, resilience and perceived social support which in turns affect their attitude towards acceptance of the help provided. Is the help available sufficient and suitable?